PROGRAM PANCA JIWA SATRI PONDOK PESANTREN ANNAKHIL DARUNNAJAH - Abadi, Abadi; Nursasongko, Rambat (Manajer Pendididikan, 2025)
This research examines the implementation of the Panca Jiwa Program at the Annakhil Darunnajah Islamic Boarding School 6 Mukomuko, Bengkulu, which includes five main values: sincerity, simplicity, independence, ukhuwah Islamiyah, and freedom. Through qualitative methods, it was found that these values ​​were implemented through student activities, OSDA, and graduate service. Support from all elements of the lodge and routine activities are the main supporting factors, even though there are obstacles to limited resources and consistency of implementation. As a result, the Panca Jiwa Program is effective in shaping the character of students, but evaluation and monitoring need to be improved to optimize the program.